Hey, Whipple, squeeze this! the classic guide to creating great advertising - Sullivan, Luke.; Bennett, Sam.; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2012)
"The classic (and irreverent) bestselling guide to creating great advertisingHey Whipple, Squeeze This has inspired a generation of ad students, copywriters, and young creatives to make their mark in the industry. But students need new guidance to ply their craft now in the digital world. This new fourth edition explains how to bring brand stories into interactive, dynamic places online, in addition to traditional television, radio, print, and outdoor ads.Creativity is still king, but this new edition contains: Important new chapters and updates that bring Whipple into the new digital world New content and examples for how to use social media and other emerging platforms Illustrate what's changing in the new world of advertising--and what isn't Hey Whipple, Squeeze This! will help sharpen your writing chops, unleash your creativity, and help raise the level of your work from hack to master craftsman"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Advertising copy; Electronic books